Postoperative mortality after a hip fracture over a 15-year period in Denmark: a national register study - Gundel, Ossian; Thygesen, Lau Caspar; Gögenur, Ismail; Ekeloef, Sarah (Acta Orthopaedica, 2019)
Background and purpose — In Denmark, 44 per 10,000 persons over the age of 50 years suffered a hip fracture (HF) in 2011. We characterized the patients and identified risk factors associated with 30-day, 90-day, and 1-year postoperative mortality in Denmark from 2000 to 2014. Patients and methods — The study builds upon data from the Danish National Patients Register and the National Causes of Death Register including all acute hospitalized HF patients aged 18 years and above. Outcomes were 30-day, 90-day, and 1-year postoperative mortality. Mortality risk was analyzed with a univariable and multivariable Cox regression including predefined variables. Results — 113,721 acute hospitalized HF patients were admitted to Danish hospitals between 2000 and 2014. The 30-day mortality risk was 9.6%, 16% at 90 days, and 27% at 1 year after HF surgery. Mortality risk was similar from 2000 to 2014 while the median lengths of stay declined from 14 (IQR 8–25) to 8 (IQR 5–11) days. Male sex, increasing age, higher Charlson Comorbidity Index, per- and subtro- chanteric fracture, and operation type other than total hip arthroplasty were independently associated with postoperative mortality. Interpretation — Short- and long-term mortality was high after hip fracture surgery and did not decline in Denmark from 2000 to 2014.